Prevailing Indigenous Filipino Rice-Based Food Processing Practices in Cayagan Valley Region, Philippines - Ibañez, Arthur G. (The PASCHR journal, 2020)
This paper discusses the Prevailing Indigenous FILIPINO RICE-BASED FOOD PROCESSING PRACTICES IN CAGAYAN VALLEY REGION, PHILIPPINES. It determines the prevailing indigenous rice-based food processing in the Cagayan Valley Region and compared it with the modern rice-based food processing technology. The descriptive research is utilized in the study covering four (4) provinces of Region 02 except Batanes. The respondents are 227 producers of rice-based products. Data was gathered through a questionnaire pre-tested using Cronbach’s alpha. Data were treated using frequency and percentages. Findings are: There are century-old prevailing traditional and indigenous existing food processing practices in Region 02, and such practices are part of the culture and tradition of rice-based food processing. In conclusion, more rice-based producers are utilizing indigenous processes rather than modern equipment and facilities in their production system.